THE ROLE OF SOCIAL INTELLIGENCE IN PERSONALITY MATURITY - Umirovich, Avlaev Orif; Abdumajitovna, Abdujalilova Shoira (International Journal of Psychosocial Rehabilitation, 2020)
The issues of personality maturity are extensively studied in foreign psychology, and they are studied based on different theories, concepts, approaches, positions, and orientations. There is also a scientific analysis of the relation of personality maturity with social intelligence. This article explores the correlation relationships between social intelligence and other types of intelligence in personality maturity. Psychological analysis of the results was performed.